Chapter 21 The Pandemic as we know it A policy studies perspective on ignorance and nonknowledge in COVID- 19 governance - Paul, Katharina T. (Taylor & Francis, 2023)
"Once treated as the absence of knowledge, ignorance has now become a highly influential and rapidly growing topic in its own right. This new edition of the seminal text in the field is fully revised and includes new and expanded chapters on religion; domestic law and jurisprudence; sexuality and gender studies; memory studies; international relations; psychology; decision-theory; and colonial history. The study of ignorance has attracted growing attention across the natural and social sciences where a wide range of scholars explore the social life and political issues involved in the distribution and strategic use of not knowing. This handbook reflects the interdisciplinary field of ignorance studies by drawing contributions from economics, sociology, history, philosophy, cultural studies, anthropology, feminist studies, and related fields to serve as a path-breaking guide to the political, legal and social uses of ignorance in social and political life. This book will be indispensable for anyone seeking to understand the important role played by ignorance in contemporary society, culture and politics."